Changes in rheology, quality, and staling of white breads enriched with medium-polymerized inulin - Barros, Jefferson HT [UNESP]; Franco, Celia ML [UNESP] (SAGE Publications, 2021)
The objective of this study was to evaluate the changes that occurred during processing white breads enriched with 5, 7.5, and 10% of medium-polymerized inulin (MPI). Farinographic analysis revealed that enrichment caused the development time and dough stability to increase by up to 69.9% and 62.8%, respectively, when 7.5% of MPI was incorporated into wheat flour. This indicated that the added MPI strengthened the doughs. Conversely, alveographic analysis demonstrated that MPI was harmful to the gluten network. The specific volume and humidity of breads with up to 7.5% MPI were similar to those of the control (MPI-free) bread. During bread storage for 10 days, we noticed that the retrogradation rate increased only for the bread sample with 10% MPI. However, MPI enrichment, regardless of concentration, promoted an increase in the Avrami exponent and affected bread firmness. Bread staling analysis indicated that the moisture difference between crumb and crust was higher for the MPI-enriched breads than for the control. Moreover, we prepared more consistent doughs and fresh breads with MPI contents of up to 7.5%, which presented good quality and were good fiber sources; however, we determined that inulin did not present an anti-staling effect.
Keywords: Avrami exponent; bread staling; fiber source; Inulin; moisture gradient